9514 1404 393
Answer:
-8x^2·y·z +3y·z^2 -4y
Step-by-step explanation:
It can be helpful to make sure the variables in each term are in alphabetical order. This makes it easier to see "like" terms. The variables in each term are ...
x^2 y z
y z^2
x^2 y z
y
Only the first and third terms are like terms, so those are the only ones that can be combined. Their coefficients are -7 and -1, so sum to -8. The combined term is of highest degree, so in standard form we list that term first.
= -8x^2·y·z +3y·z^2 -4y
Hey there! :)
Area of triangles → (base × height) ÷ 2
The base and height are the 2 legs. You have to find the length of the other leg to find the area, using the Pythagorean Theorem.
a² + b² = c² → c² - a² = b²
c = 12
12² = 12 × 12 = 144
a = 10
10² = 10 × 10 = 100
144 - 100 = 44
√44 = 6.6
_____________________________________________________________
Area of triangles → (base × height) ÷ 2
Base: 10
Height: 6.6
6.6 × 10 = 66
66 ÷ 2 = 33
The area is 33
Hope this helps :)
-1/2 ans. Hope it helps..
Step-by-step explanation:
h(x) = 1/4 x
tha is the answer